DISCRIMINANT FACTORS AFFECTING CHEATING BEHAVIOR IN IPS (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
The results of the study found that: First, self-confidence (X1) has a significant effect on cheating behavior with a regression coefficient of -0.557. The value of this coefficient is significant because the value of t arithmetic is 4.692, t table is 1.66691, which means that self-confidence increases by one unit. then cheating behavior will increase by -0.557. Academic procrastination (X2) has a significant effect on cheating behavior with a regression coefficient of -0.482. The coefficient value is significant because the t arithmetic value is 4.339, t table is 1.66691, it means that if it is academic procrastination. then cheating behavior will increase by -0.482. Third, peer conformity (X3) has a significant effect on cheating behavior with a regression coefficient of -0.379. This coefficient value is significant because the t-count value is 3.333, t-table is 1.66691, meaning that peer conformity increases by one unit. the behavior of cheating purchases of -0.379. The four learning interests (X4) have a significant effect on cheating behavior with a regression coefficient of -0.507. The value of this coefficient is significant because the value of t arithmetic is 3.612, t table is 1.66691, it means that learning interest increases by one unit. will increase cheating behavior by -0.507. Five School Disciplines (X5) have a significant effect on cheating behavior with a regression coefficient of -4.33. This coefficient value is significant because the t arithmetic value is 4.022 > t table 1.66691, which means that one unit of School Discipline will increase cheating behavior by -4.33. The six product quality, the effect of self-confidence, academic procrastination, peer conformity, learning interest and school discipline on cheating behavior with an F value of 18.302≥ F table 2.35 and significant 0.000 <0.05.